Electrocatalysis: Kinetic Enhancement of Sulfur Cathodes by N‐Doped Porous Graphitic Carbon with Bound VN Nanocrystals (Small 48/2020). Issue 48 (3rd December 2020) - Yang, Xinyue; Chen, Shang; Gong, Wenbin; Meng, Xiaodong; Ma, Junpeng; Zhang, Jie; Zheng, Lirong; Abruña, Héctor D.; Geng, Jianxin
Abstract : In article number 2004950, Héctor D. Abruña, Jianxin Geng, and co‐workers invent one‐pot strategy to synthesize N‐doped porous graphitic carbon with bound VN nanocrystals (3D VN@N‐PGC) from glucose as the C source, urea as the N source, and NH4 VO3 as the V source. The 3D VN@N‐PGC as sulfur host shows superior electrocatalytic effects on the cathode reactions of Li–S batteries.